Optimal configuration of diversified energy storage for renewable energy peak regulation and frequency response (International Conference on Energy, Intelligence Systems, and Cloud Computing (Ingenio 2026), 2026)
Faced with the uncertainty and volatility that large-scale integration of renewable energy brings to the power grid, implementing combined electricityheat scheduling within the park is highly beneficial. Therefore, a comprehensive energy storage configuration method is proposed for the park based on various types of energy storage resources, which includes wind turbine (WT), photovoltaic unit (PV), electro-chemical energy storage (ECES), and solid-state electric thermal storage (SETS). To maximize the profit of the park, revenue from the electricity market, ancillary services, and capacity market is considered to develop a configuration method and profit, while calculating investment and operation costs. Compared with traditional methods, four different configuration scenarios are selected for simulation calculations based on energy spatiotemporal conversion characteristics, and energy storage facilities with ancillary service capabilities can effectively improve the park's economy. STES cannot obtain sufficient revenue under the current pricing mode. However, the combined electric-heat energy storage can increase the flexibility of the park, its economic feasibility still needs to be judged based on the actual situation.